Pengaruh Marketing Strategy, Sistem Informasi Geografis dan Digitalisasi Terhadap Peningkatan Daya Saing (Studi pada Kedai ONOFF) - Abdillah, Achmad Fikri Abil; Susyanti, Jeni; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze the influence of marketing strategies, geographic information systems (GIS), and digitalization in enhancing business competitiveness, with a case study on the OnOff store. Effective marketing strategies, such as product positioning, pricing, promotion, and distribution channels, play a crucial role in attracting and retaining customers and driving business growth. The implementation of GIS enables businesses to gain spatial insights, optimize operations, conduct market segmentation, and allocate resources efficiently, which can enhance competitiveness. Digitalization has also become an important factor in today's business landscape, where companies must continually adapt their strategies to maintain a competitive advantage. Keywords: Marketing Strategy, Geographic System Information, Digitalization, and Enhancement of Competitiveness